The relationship between international financing and domestic investment efficiency in Financing Development in the State of Palestine - Qabaha, Mahmoud Gawdat Mahmoud; Shobaki, AbdulRahim Salim (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the relationship between international financing and the efficiency of local investment in financing development in the State of Palestine. The study followed the descriptive analytical approach. The main problem of the study lies; In that, despite the importance of international funding for the Palestinian people and their development, the completion of projects, the reduction of unemployment, and the stimulation of the local investment environment in order to lead to the self-empowerment of the Palestinian economy, if it was used properly, the international funding provided to the Palestinian state over the past years did not bear fruit and did not achieve the Palestinian aspirations represented in shifting the compass of the Palestinian economy towards its correct direction on the path of economic growth and comprehensive and sustainable development. The study concluded several results, most notably; International financing has several positive advantages towards Palestinian domestic and economic investment, but this does not mean that it does not have negative aspects on several Palestinian sectors that negatively affect strategic plans and comprehensive and sustainable development processes, in addition to the lack of an atmosphere of democracy and equality in the Palestinian sector, and the high rate of Exacerbation of corruption in the joints of the state, which negatively affects local investments and international financing, and there is a large gap between theory and practice in the Palestinian government’s approach, public policies, and development plans. Moreover, the Israeli occupation remains a major obstacle to economic liberation and the Palestinians’ achievement of their desired goals of self-financing. And liberation from international dependence and excessive financing, and the ominous Palestinian division negatively affected international financing and creating the elements of the environment and climate that stimulates local investment and its efficiency.
Keywords: local financing; local investment; development